2022
DOI: 10.3389/fenvs.2022.977198
|View full text |Cite
|
Sign up to set email alerts
|

County carbon emissions in the Yangtze River Delta region: Spatial layout, dynamic evolution and spatial spillover effects

Abstract: The Yangtze River Delta region contributes nearly 16% of the national carbon emissions and is the key area for carbon emission reduction in China. Accurately grasping the spatial evolution characteristics of carbon emissions and the interaction between counties and regions is of great practical significance for precise and collaborative carbon reduction. This study firstly explores the spatial layout and dynamic evolution characteristics of county carbon emissions in the Yangtze River Delta region from 2000 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
(46 reference statements)
0
1
1
Order By: Relevance
“…The study found that carbon emissions in the CAYRDUA have slowed down since 2011, which is consistent with previous studies. Wei et al suggested that carbon emissions in the YRDUA were around 1.6 billion tons after 2011 [59], whereas this study indicates that the total carbon emissions in the study area stabilized at around 1.2 billion tons. This difference can be attributed to the different scopes of urban agglomeration.…”
Section: Discussioncontrasting
confidence: 68%
“…The study found that carbon emissions in the CAYRDUA have slowed down since 2011, which is consistent with previous studies. Wei et al suggested that carbon emissions in the YRDUA were around 1.6 billion tons after 2011 [59], whereas this study indicates that the total carbon emissions in the study area stabilized at around 1.2 billion tons. This difference can be attributed to the different scopes of urban agglomeration.…”
Section: Discussioncontrasting
confidence: 68%
“…However, existing work focuses on the division of the study area according to its geographical conditions. For instance, in China, the carbon emission features of the eastern, middle and western regions have been researched 51,52 . Other study regions in terms of carbon emission features include the Yellow River 53 , Yangtze River 52 , Beijing-Tianjin-Hebei region 54 and some provinces 25,55 .…”
Section: Spatiotemporal Differences In and Influencing Effects Of Per...mentioning
confidence: 99%
“…The R 2 and log likelihood parameters of SDM with the spatial fixed effect of industrial agglomeration on industrial SO 2 emissions are the largest, and the R 2 and Log likelihood parameters of SDM with the spatial fixed effect of industrial agglomeration on industrial soot emissions are the largest. Therefore, the SDM with spatial fixed effect is used to estimate the impact of industrial agglomeration on industrial wastewater emissions, industrial SO 2 emissions, and industrial soot emissions (58). According to the estimation results of SDM with fixed spatial effect, the spatial lag coefficients of industrial wastewater emissions, industrial SO 2 emissions, and industrial soot emissions are 0.202, 0.244, and 0.230, respectively, and they are all significantly positive at the 1% level (Table 7).…”
Section: Spatial Econometric Regression Resultsmentioning
confidence: 99%